2004
DOI: 10.1111/j.1540-8167.2004.03356.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic Versus Fluoroscopic Mapping for Catheter Ablation Procedures:

Abstract: For all catheter ablation procedures, even when a center's "learning curve" for CARTO is included, procedure duration and outcome are similar for CARTO and conventional procedures. CARTO is associated with drastically reduced fluoroscopy time and radiation dose. Although fewer catheters are used with CARTO, catheter costs remain higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 23 publications
2
82
0
2
Order By: Relevance
“…740,741,742 However, several studies performed to define the clinical benefit of EAM systems have generated mixed results: whereas some studies have reported that use of these mapping systems with or without image integration improves the safety and efficacy of AF ablation, other studies have reported contradictory findings. 743,744,745,746,747 Obviously, the use of 3D mapping systems will increase the cost of the procedure.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…740,741,742 However, several studies performed to define the clinical benefit of EAM systems have generated mixed results: whereas some studies have reported that use of these mapping systems with or without image integration improves the safety and efficacy of AF ablation, other studies have reported contradictory findings. 743,744,745,746,747 Obviously, the use of 3D mapping systems will increase the cost of the procedure.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…8, 9 The reduction greatly benefits patients, physicians and a wide range of laboratory staff members because estimates of between 0.3 and 2.3 excess fatal malignancies per 1,000 patients for each hour of fluoroscopy have been reported. 8, 9 There are advantages and drawbacks of each 3-D mapping system (Table). In all the systems, dislocation of the positional reference causes a miss-alignment of the geometry map.…”
Section: Non-contact Mapping Systemsmentioning
confidence: 99%
“…Moreover, radiation exposure during AF ablation is longer than simpler catheter ablation procedure [20,21]. EAM systems have been demonstrated to reduce fluoroscopy times during RF ablations [22][23][24]. Our results imply that the respiratory gating provides further reduction in fluoroscopy time.…”
Section: Safetymentioning
confidence: 67%